Attack : with a National 'Clean Throat' campaign / by A, Corbett-Smith - Corbett-Smith, Arthur, 1879-
1929-10 1929 1920s 9 pages To keep his body in sound health is the first duty of a good citizen. And no man or woman can set himself a nobler task than actively to further the health of his fellows. MY PROPOSAL What, then, do I propose? I propose, for a start, the immediate organisation of a National "Clean Throat" Week. The date might suitably be December 1 or December 8. The critical illness period is January to March. For such a Week we shall have in certain co-operation and support the entire leadership of the nation, H.M. Government, the Church of all denominations, the leaders of Commerce and Industry, the Medical and Dental services, the Press, Local Government Authorities, the Bar and the Stage, the Admiralty, the Air Ministry and Army Council, the Radio Service and the Cinema industry. We should organise all these activities into a cyclone of publicity. For the first time national attention will be focussed. Thereafter, plans for further and continuous developments in enlightenment may be discussed. A PERSONAL NOTE To this end I am proud to offer my services as Honorary Organiser. Why? Because enlightenment and inspiration of the People is the task to which I have devoted my life's work. In this present campaign I have the inestimable advantage of not being a medical man. It was for that reason, in 1913, I was able to initiate the national enlightenment campaign in the Venereal Diseases. It is mainly because I was an Army officer that I was able to convince the People on the subject of England's Sea Affair. Besides, Louis Pasteur, one of the most honoured of all names in medicine, was not a medical man. ZERO HOUR For the suggested campaign the present moment is most opportune. Shall we make December 1 "zero hour" ? And shall we echo the ardent words with which General Foch opened the great and decisive victory of the Marne in September, 1914? "My right wing is broken. My centre is in retreat. The situation is excellent. I SHALL ATTACK !" October 14, 1929. A.C-S. Address, see overleaf 4 200/B/3/2/C693/3/13